Survey of Rice Pests, Diseases and Natural Enemies on “Upsus” Program in Karawang District, West Java Province - Kurniawan Effendi; Abdul Munif; I Wayan Winasa (Jurnal Perlindungan Tanaman Indonesia, 2020)
"Upsus" (Special Efforts) Program is a program to increase crop production and productivity to support the acceleration of food self-sufficiency held by the government. The targets are to increase the planting index (IP) by 0.5 and productivity by 0.3 ton/ha/Harvested Dry Grain (HDG). Increased productivity has not been reached optimally. This research aimed to determine the number/types of the dominant pests and natural enemies, and pests and diseases attack rates in the wetland rice plantation "Upsus" Program in Karawang District. Direct observation was carried out on four stages of plant development, in the nursery stage (10–14 days after sowing) 200–300 m², seedlings stage (10–20 days after planting), vegetative stage (5–6 weeks after planting), and reproductive stage (1–2 weeks after flowering) respectively within an area of 2000 m². Twenty samples were observed in the nursery stage and 50 samples in the following stages. The dominant pests and diseases found were Nilaparvata lugens, Leptocarisa oratorius, Schirpophaga incertulas, Cnaphalocrocis medinalis, Scotinophara coarctata, Mythimna separata, bacterial leaf blight (Xanthomonas. oryzae pv. oryzae), blast (Pyricularia grisea) and narrow brown spot (Cercospora oryzae). The recorded dominant natural enemies were Cyrtorhinus sp., Paederus sp., Tetragnatha sp., and Pardosa pseudoannulata. S. incertulas showed the highest attack intensity and the highest disease severity was found in bacterial leaf blight. The largest population of dominant pests and natural enemies was found in the generative stage. The high application of pesticides affected the population of pests, natural enemies, and the level of pest and disease attacks.